Biomass‐Derived Aromatics by Solid Acid‐Catalyzed Aldol Condensation of Alkyl Methyl Ketones. (24th June 2020) - Reif, Phillip; Rosenthal, Hannah; Rose, Marcus
Abstract: Cyclotrimerization of biomass‐based alkyl methyl ketones exhibits great potential as a route to biomass‐derived aromatics by a sustainable valorization of biorefinery streams. In this study, acetone is used as a model reagent to screen solid acid catalysts for the aldol condensation reaction to the aromatic trimer mesitylene. From a broad catalyst screening promising activity is shown by the cation exchange resin Purolite CT275DR, the beta‐zeolite H‐BEA 35, and aluminosilicate Siralox 70/170 HPV which are used to further investigate reaction parameters. Acetone conversion and mesitylene yield increase with temperature and time, while yield of the intermediate mesityl oxide decreases. This effect is also found for higher quantities of catalyst acid sites and is accompanied with an increased side product formation which negatively affects total product selectivity. Analyzing the reaction progress shows a significant drop in catalyst productivity after an initial start‐up phase. This observation is linked to a deactivation of the catalyst which involves water that is formed during the condensation reaction of acetone. Obtained results confirm the general viability of the aromatization of alkyl methyl ketones and can be considered the first step to an alternative sustainable route to biomass‐derived aromatics compared to other currently discussed routes. Abstract : A novel route for sustainable production of 1, 3, 5‐substituted C6 ‐aromatics by cyclotrimerization of biomass‐based alkyl methyl ketones via aldol condensation is presented. Screening results for suitable solid acid catalysts and influence of reaction parameters temperature and time are discussed. Temporal progress of the reaction and possible causes for observed catalyst deactivation are studied.